SDHB immunohistochemistry for prognosis of pheochromocytoma and paraganglioma: A retrospective and prospective analysis - Su, Tingwei; Yang, Yifan; Jiang, Lei; Xie, Jing; Zhong, Xu; Wu, Luming; Jiang, Yiran; Zhang, Cui; Zhou, Weiwei; Ye, Lei; Ning, Guang; Wang, Weiqing (Frontiers in Endocrinology, 2023)
Pheochromocytomas and paragangliomas (PCC/PGL) are rare neuroendocrine tumors and can secrete catecholamine. Previous studies have found that SDHB immunohistochemistry can predict SDHB germline gene mutation, and SDHB mutation is closely associated with tumor progression and metastasis. This study aimed to clarify the potential effect of SDHB immunohistochemistry as a predictive marker for tumor progression in PCC/PGL patients. We included PCC/PGL patients diagnosed in Ruijin Hospital, Shanghai Jiao Tong University School of Medicine from 2002 to 2014 for retrospective analysis and discovered that SDHB (-) staining patients had poorer prognoses. Then we examined SDHB protein expression by immunohistochemistry on all tumors in the prospective series, which was composed of patients from 2015 to 2020 in our center. In the retrospective series, the median follow-up was 167 months, and during follow-up, 14.4% (38/264) patients developed metastasis or recurrence, and 8.0% (22/274) patients died. Retrospective analysis revealed that 66.7% of participants in the SDHB (-) group and 15.7% of those in the SDHB (+) group developed progressive tumors (OR: 10.75, 95% CI: 2.72-52.60, P=0.001), and SDHB (-) was independently associated with poor outcomes after adjusting by other clinicopathological parameters (OR: 11.68, 95% CI: 2.58-64.45, P=0.002). SDHB (-) patients had shorter disease-free survival and overall survival (P<0.001) and SDHB (-) was significantly associated with shorter median DFS (HR: 6.89, 95% CI: 2.41-19.70, P<0.001) in multivariate cox proportional hazard analysis. In the prospective series, the median follow-up was 28 months, 4.7% (10/213) patients developed metastasis or recurrence, and 0.5% (1/217) patient died. For the prospective analysis, 18.8% of participants in the SDHB (-) group had progressive tumors compared with 3.6% in the SDHB (+) group (RR: 5.28, 95% CI: 1.51-18.47, P=0.009), statistical significance remained (RR: 3.35, 95% CI: 1.20-9.38, P=0.021) after adjusting other clinicopathological factors. Our findings demonstrated patients with SDHB (-) tumors had a higher possibility of poor outcomes, and SDHB immunohistochemistry can be regarded as an independent biomarker of prognosis in PCC/PGL.